2022
DOI: 10.1139/cjz-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

What do caribou eat? A review of the literature on caribou diet

Abstract: Historically the study of diet caribou and reindeer (Rangifer tarandus (Gmelin, 1788)) has been specific to herds and few comprehensive circumpolar analyses of Rangifer diet exist. As a result, the importance of certain diet items may play an outsized role in the caribou diet zeitgeist, e.g., lichen. It is incumbent to challenge this notion and test the relevant importance of various diet items within the context of prevailing hypotheses. We provide a systematic overview of 30 caribou studies reporting caribou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 82 publications
1
24
1
Order By: Relevance
“…In arctic and subarctic regions, the potential for exploitative competition among herbivores should thus be higher during winter, when resource availability is limited (Thing 1977). We found that spatial overlap between both species was low during winter, when lichen is the predominant food item in caribou's diet (Webber et al 2022). Caribou wintering grounds in the taiga are mostly south of the area where muskoxen occur.…”
Section: Discussionmentioning
confidence: 97%
“…In arctic and subarctic regions, the potential for exploitative competition among herbivores should thus be higher during winter, when resource availability is limited (Thing 1977). We found that spatial overlap between both species was low during winter, when lichen is the predominant food item in caribou's diet (Webber et al 2022). Caribou wintering grounds in the taiga are mostly south of the area where muskoxen occur.…”
Section: Discussionmentioning
confidence: 97%
“…Foraging apart from conspecifics reduce the costs of competition at cratering sites, which may be limited on the landscape or relatively small. We propose that while caribou generally have larger group sizes in winter (Webber &Vander Wal, 2021), groups vary in size based on movement and habitat selection behaviour presumably to balance the trade-off between competition and information acquisition. Furthermore, female caribou often have antlers, which unlike males, persist into winter.…”
Section: Discussionmentioning
confidence: 99%
“…Caribou live in fission-fusion societies (Lesmerises, Johnson, & St-Laurent, 2018), and throughout much of their range, caribou forage primarily on lichen, grasses, sedges, and other deciduous browse with access to these resources changing between the seasons (Bergerud, 1974). During winter (January to March), the landscape is covered by snow, and caribou forage primarily on lichen (Webber, Ferraro, Hendrix, & Vander Wal, 2022). Lichen is heterogeneously distributed, and access is impeded by snow and ice cover.…”
Section: Caribou As a Model Systemmentioning
confidence: 99%
“…Caribou diet changes seasonally based on the accessibility of resources. During summer, caribou are generalists, foraging on shrubs, lichens, sedges, and herbaceous plants (Bergerud & Nolan, 1970; Webber et al, 2022). During winter, they either dig holes in the snow termed craters and consume terrestrial lichens, or forage on arboreal lichens when access to terrestrial lichens is hindered by the snow depth or its hardness (Johnson, Parker, & Heard, 2001).…”
Section: Methodsmentioning
confidence: 99%